Evaluation of six aromatic rice varieties for yield and yield contributing characters - Md Ashrafuzzaman,; Md Rafiqul Islam,; Ismail, Mohd Razi; Shahidullah, S. M.; Musa, Mohamed Hanafi (2009)
A study was undertaken to evaluate the growth performance and grain quality of six aromatic rice varieties BR34, BR38, Kalizira, Chiniatop, Kataribhog and Basmati grown under rainfed conditions. The rice varieties differed significantly (P<0.05) with respect to leaf chlorophyll content, plant height, internode length, thousand grain weight and grain and straw yields. Varieties differed in morphological and yield and yield contributing traits. Thousand grain weight and grain yield both were highest in BR38. Basmati required shorter days to maturity and Kalizira longest days to maturity.